Understanding Student perception regarding the use of chatGPT in their argumentative writing: A qualitative inquiry - Ahmad Azmi Abdel Hamid Esmaeil,; Dg Norizah Ag Kiflee@Dzulkifli,; Ismail Maakip,; Sanen Marshall,; Ovelyn Ozy Matanluk, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study is a qualitative study to understand perception regarding the use of ChatGPT in their argumentative writing. Argumentative writing equips students with the opportunity to emulate scientists, allowing them to collect data, analyse, and justify their findings while addressing research questions. This method has been proven to enhance both their learning and critical thinking abilities. However, with the rise of AI tools like ChatGPT, which are becoming increasingly popular among university students, concerns have emerged about their potential impact on students' capacity to craft argumentative papers. This study delves into these concerns, focusing on students' perceptions of ChatGPT's role in their argumentative writing endeavours. Employing qualitative research methods, seventeen students were selected as respondents using purposive sampling. The respondents were tasked with reflecting on this issue. The results from the analysis of documents indicated that although students acknowledge the extensive capabilities of ChatGPT, including its ability to provide information and guidance and decrease both research expenses and time consumption, they also voice apprehensions. These include doubts about ChatGPT's accuracy, potential over-reliance which could diminish their learning and critical thinking, and the looming risk of plagiarism. The study suggests that while embracing these tools can help produce meaningful argumentative writing more efficiently, caution must be taken to avoid unchecked use of ChatGPT in writing.